Whole‐Cell P450 Biocatalysis Using Engineered Escherichia coli with Fine‐Tuned Heme Biosynthesis (Adv. Sci. 6/2023). Issue 6 (24th February 2023) - Hu, Baodong; Yu, Haibo; Zhou, Jingwen; Li, Jianghua; Chen, Jian; Du, Guocheng; Lee, Sang Yup; Zhao, Xinrui
Abstract : Whole‐Cell Biocatalysts In the article 2205580, Xinrui Zhao and co‐workers report an engineered Escherichia coli strain capable of improved heme supply suitable for whole‐cell P450 biocatalysis. The intracellular heme level is fine‐tuned by the combined use of mutated heme‐sensitive biosensor and small regulatory RNA systems.